The Effect Of Perceived Value On Repurchase Intention Of Skechers Shoe Products With Brand Love As A Mediating Variable - Putri Rahmadani; Barkah Barkah; Juniwati Juniwati; Ramadania Ramadania (UNIVED Press, 2025)
This study aims to analyse the effect of Perceived Quality Value, Perceived Social Value, and Perceived Emotional Value on Repurchase Intention with Brand Love as a mediating variable in purchasing Skechers shoes. Samples were taken using purposive sampling technique, with a total of 150 respondents. The data analysis method uses a Structural Equation Model (SEM) based on Partial Least Square (PLS) with SmartPLS 4.0 software. The results of the discussion show that Perceived Quality Value, Perceived Social Value, and Perceived Emotional Value have a significant effect on Repuchase Intention through the mediation of Brand Love. These findings emphasise the importance of marketing strategies that focus on improving product quality, social value, and emotional value to strengthen brand loyalty and drive repurchase value.